2021
DOI: 10.1101/2021.08.10.21261758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“At that moment, understanding the donation is crucial to make a decision”:A qualitative study exploring the process of postmortem brain tissue donation after suicide

Abstract: Background: The direct examination of postmortem brain tissue can provide valuable help in refining knowledge on the pathophysiology and genetics of neuropsychiatric disorders. Obtaining postmortem consent for the donation of brain tissue after death by suicide can be difficult, as families may be overwhelmed by a violent and unexpected death. Examining the process of brain donation can inform on how the request can best be conducted, examining the existing barriers and enhancing communication, to the benefit … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 94 publications
(200 reference statements)
0
3
0
Order By: Relevance
“…In the work of Moules et al on paediatric cell lines, parents reported being comforted by the knowledge that their child was ‘living on’ in the tumour cell line [ 11 ] referencing a sense of connection to the culture. This is a sentiment echoed in numerous other studies, both oncology and non-oncology such as Padoan et al [ 31 ] and ties in with broad references throughout the wider brain donation literature to living on and legacy being a primary benefit [ 11 , 12 , 16 , 31 , 49 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the work of Moules et al on paediatric cell lines, parents reported being comforted by the knowledge that their child was ‘living on’ in the tumour cell line [ 11 ] referencing a sense of connection to the culture. This is a sentiment echoed in numerous other studies, both oncology and non-oncology such as Padoan et al [ 31 ] and ties in with broad references throughout the wider brain donation literature to living on and legacy being a primary benefit [ 11 , 12 , 16 , 31 , 49 ].…”
Section: Discussionmentioning
confidence: 92%
“…Of the 8 studies with data specifically collected from bereaved adult NOK (Eatough 2012, Fonseca 2015, Azizi 2006, Millar 2007, Sundqvist 2012, Garrick 2009, Millar 2008 and Padoan 2021), 4 studies [ 16 , 35 , 39 , 49 ] indicated that NOK in this state see brain donation as a practical focus in their time of grief, providing a sense of control, a distraction and an empowering process enabling them to fulfil a wish. This insight was not noted as a potential benefit in the studies including NOK prior to donation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation